Josephus on the Servile Origins of the Jews - Friedman, David A. (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2014)
The story of the Israelites’ slavery in Egypt and subsequent redemption is the central narrative element of the Pentateuch. Josephus’ claim that he was providing an accurate account of the Jews’ ancient history in Jewish Antiquities thus meant that he had to address the Jews’ servile origins; however, first-century Roman attitudes toward slaves and freedmen would have made this problematic for ideological and political reasons. Although Josephus added references to Jews’ slavery to the account of Jewish history in Jewish Antiquities, he appears deliberately to downplay the Jews’ servile origins at key parts of the narrative, including God’s promise to Abraham in Gen 15 and the account of the Jews’ enslavement in Exod 1. Josephus also demonstrates a concern with the servile status of Jacob’s secondary wives Zilpah and Bilhah. The account of Joseph’s life in Jewish Antiquities emphasizes his non-servile qualities and his chance enslavement. Roman hostility to slaves and freedmen, Josephus’ own personal experience of captivity, and the likely presence in Rome of Jewish freedmen might explain Josephus’ sensitivity to the Jews’ servile origins.